An ethnobotanical study of medicinal plants used to treat and manage diabetes mellitus in Ede, Osun State Nigeria - Ajao, Abdulwakeel Ayokun-nun; Mukaila, Yusuf Ola; Kenkpen, David Yahn (Ethnobotany Research and Applications, 2023)
Background: The severity and relatively high incidence of diabetes mellitus (DM) in Nigeria call for research into discovering more potent antidiabetic agents. People of Ede have a long history of relying on medicinal plants to treat and manage various ailments, including DM. Therefore, it provides an alternative means of managing and treating the condition. This study was carried out to identify and document medicinal plants used in treating DM among the inhabitants of Ede, southwestern Nigeria. Methods: A preliminary survey of the study area was conducted between August 2022 and February 2023. One hundred thirty-five people were selected for semi-structured interviews and questionnaires to collect ethnobotanical data, including the local names of the plants, the plant parts used, and methods of preparation. A literature survey was also conducted to determine which recorded plants have been validated scientifically for their traditional use in treating DM. Results: Thirty-nine plants from 24 families were identified from the survey. Crinum jagus from the family Amaryllidaceae has the highest citation and fidelity level frequency. Trees (46%) and shrubs(23%) were the most abundant life forms of the recorded plants. Similarly, leaf (43%) and stem bark (19%) were the most used plant part, while decoction (54%) was the favoured method of preparation. Over 87% of the plants have been assessed for antidiabetic activities, thus lending credence to the usage of the implicated plants for DM. Conclusion: This study indicates that the area has a rich diversity of medicinal plants for treating and managing DM. Therefore, phytochemical, pharmacological, and toxicological screening of plants that have not been tested is recommended to aid the ongoing search for effective and safe antidiabetic agents. Keywords: Antidiabetic activities, Diabetes mellitus, Ede, Ethnobotany, Indigenous knowledge, Medicinal plants